Wireless communication and networks (Oxford University Press, 2015)
Annotation Wireless Communication and Networks is designed as a textbook for students of electronics and communication engineering as well as computer engineering. The book provides a detailed and holistic coverage of the various aspects and technologies of wireless systems as well as emerging systems and standards.
Keywords: Wireless communication systems.; elektronické knihy; electronic books